2020
DOI: 10.7759/cureus.8687
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Operative Corridor in Oblique Lumbar Interbody Fusion Between Preoperative Magnetic Resonance Imaging and Intraoperative Cone-Beam Computed Tomography Using Morphometric Analysis

Abstract: Background The oblique lumbar interbody fusion or anterior-to-psoas (OLIF/ATP) technique relies on a corridor anterior to the psoas and posterior to the vasculature for lumbar interbody fusion. This is evaluated preoperatively with CT and/or MRI. To date, there have been no studies examining how intraoperative, lateral decubitus positioning may change the dimensions of this corridor when compared to preoperative imaging. Objective Our objective was to evaluate changes in the intraoperative corridor in the supi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(32 reference statements)
2
5
0
1
Order By: Relevance
“…Several prior studies have also assessed the safe interval between the iliac vessels or aorta and the anteromedial border of the psoas muscle during oblique lateral interbody fusion (OLIF) and these studies have shown significant changes in the safe interval, dependent both on patient positioning (supine vs lateral decubitus) and hip flexion vs extension. [26][27][28] Taking into consideration the results noted in the previously mentioned studies, 18,[25][26][27][28] it is likely that the more posterior location of the femoral nerve in the prone position compared to the lateral decubitus position, as seen in our study, is primarily the result of hip extension in the prone position and hip flexion in the lateral decubitus position. Based on the results of this study, the safe working corridor at the L4-L5 level may be larger when performing prone, as opposed to laterally positioned, LLIF.…”
Section: Discussionsupporting
confidence: 57%
“…Several prior studies have also assessed the safe interval between the iliac vessels or aorta and the anteromedial border of the psoas muscle during oblique lateral interbody fusion (OLIF) and these studies have shown significant changes in the safe interval, dependent both on patient positioning (supine vs lateral decubitus) and hip flexion vs extension. [26][27][28] Taking into consideration the results noted in the previously mentioned studies, 18,[25][26][27][28] it is likely that the more posterior location of the femoral nerve in the prone position compared to the lateral decubitus position, as seen in our study, is primarily the result of hip extension in the prone position and hip flexion in the lateral decubitus position. Based on the results of this study, the safe working corridor at the L4-L5 level may be larger when performing prone, as opposed to laterally positioned, LLIF.…”
Section: Discussionsupporting
confidence: 57%
“…The authors demonstrated that the oblique corridor tends to be greater on the left side and that it gradually decreases in size the more caudal the level. 11,18 Results similar to those found in the present study, where we identified a significant difference between the size of the corridor in L3L4 and L4L5 in both positions.…”
Section: The Oblique Lateral Interbody Fusion Technique (Olif)supporting
confidence: 90%
“…Radiographic (MRI) and cadaveric studies on the surgical windows developed following transpsoas LLIF and OLIF by disk level(s) are summarized in Table 3 9,10,14,18–20 Figure 8. highlights the progressive narrowing of the safe corridors between the nerve plexus and the prevertebral vessels at the lower lumbar levels, as mapped by Moro et al 16.…”
Section: Discussionmentioning
confidence: 99%
“…Dissimilar to our left-sided premobilization measurements, the authors found that the right decubitus position increased the left prepsoas surgical window sizes at all levels between L1 and L5, with the greatest relative increase noted at L1-L2 (average 3.1 mm) and the least at L4-L5 (average 2.1 mm) perhaps owing to the increasing volume of the psoas muscle more caudally. 10 Unlike the direct manual measurement method we adopted to determine the surgical corridor sizes, in the aforementioned study measurements' overestimation is plausible due to exclusive radiographic determination and the use of dissimilar imaging modalities (preoperative MRI and intraoperative computed tomography scan).…”
Section: Radiographic and Premobilization Measurementsmentioning
confidence: 99%
See 1 more Smart Citation